Epigenetic Regulation of Inflammatory Signaling and Inflammation-Induced Cancer - Tan, Shawn Ying Xuan; Zhang, Jieqiong; Tee, Wee-Wei (Frontiers in Cell and Developmental Biology, 2022)
Epigenetics comprise a diverse array of reversible and dynamic modifications to the cell’s genome without implicating any DNA sequence alterations. Both the external environment surrounding the organism, as well as the internal microenvironment of cells and tissues, contribute to these epigenetic processes that play critical roles in cell fate specification and organismal development. On the other hand, dysregulation of epigenetic activities can initiate and sustain carcinogenesis, which is often augmented by inflammation. Chronic inflammation, one of the major hallmarks of cancer, stems from proinflammatory cytokines that are secreted by tumor and tumor-associated cells in the tumor microenvironment. At the same time, inflammatory signaling can establish positive and negative feedback circuits with chromatin to modulate changes in the global epigenetic landscape. In this review, we provide an in-depth discussion of the interconnected crosstalk between epigenetics and inflammation, specifically how epigenetic mechanisms at different hierarchical levels of the genome control inflammatory gene transcription, which in turn enact changes within the cell’s epigenomic profile, especially in the context of inflammation-induced cancer.